How interaction molds semantics: The mood functions of Chinese “sum-up” adverbs - Song, Jingyao (Frontiers in Psychology, 2022)
"Hezhe" (合着), "ganqing" (敢情), and "nao le bantian" (闹了半天) are common mood expressions in modern Chinese. Despite their various original meanings and roots, they have a common function of summarizing the information before as well as have got three pragmatic functions which emerged through the same pragmatic mechanism called "violation". These functions are: 1) "unexpectation" from the violation of psychological expectation; 2) "criticism" from the violation of universal principles; 3) "humor" from the violation of communicative principles. A statistic work of several corpora showed that these functions of the above three words appear broadly in verbal materials, with differences in their proportions according to the communication types and genres. In Chinese teaching to speakers of other languages, more attention should be paid to these words stemming from dialects, especially during intermediate and advanced levels.